Agriculture income assessment for the purpose of social assistance: The case of Ukraine - Dmytro Boyarchuk; Liudmyla Kotusenko; Katarzyna Piętka-Kosińska; Roman Semko; Irina Sinitsina (Center for Social and Economic Research (CASE), 2009)
Ukraine belongs to the group of countries which are known for the widespread phenomenon of subsistence and semi-subsistence farming. Individual farmers are not obliged to produce financial reports and their incomes belong to the category of unobservable incomes. When checking the eligibility for social assistance the level of their incomes needs to be estimated. In a country, where poverty rate is quite high, the coverage of the poor with financial aid is relatively low and public finances under constant control, the importance of a fair and justified methodology for income imputation is particularly strong. In this situation, an outdated and unfair current system of agriculture income estimation in Ukraine calls for immediate changes. This paper presents recommendations for the Ukrainian government in the area of agriculture income imputation, where several methods of estimating farm income were proposed (including the one based on Household Budget Survey). The recommendations were preceded with the analysis of five countries' practices in this area: Kazakhstan, Kyrgyzstan, Moldova, Russia, and Poland. A review of different means testing methods, including direct means testing and proxy means testing, served as an introduction to the topic.
Keywords: O18; E26; C13; Q12; I38; 330; subsistence and semi-subsistence farming; hard to verify income; farm household income; income (agro-income) imputation; means testing methods; Agrareinkommen; Subsistenzwirtschaft; Sozialpolitik; Armutsbekämpfung; Ukraine